HISTORY OF THE DEVELOPMENT OF LITERATURE AND ART IN THE OASIS OF KASHKADARYA DURING THE SOVIET PERIOD - Abdulla Akhmatov (Western European Studies, 2024)
the article discusses the history of the development of literature and art in the Kashkadarya oasis during the Soviet period
Keywords: Kashkadarya; Soviet era; oasis; literature